Exploring Same-Sex Attraction in Indonesian Churches: Teachings, Attitudes, and Experiences - Mulya, Teguh Wijaya (Faculty of Psychology, Universitas Surabaya, 2011)
The aim of this study is to explore the issue of same-sex attraction (SSA) among church members in Indonesia. Using both qualitative and quantitative method, the teaching of the leaders, attitudes of the church members, and the experiences of SSA are described. Six church leaders of six churches in Surabaya, Indonesia were interviewed in semi-structured interviews and 268 church youths filled questionnaires on SSA. The results show that the majority of church leaders and church youths have conservative attitude toward SSA. As many as 5.6% of participants have experienced SSA at a time of his/her life. Similar with Indonesian church youths in general, most of them agree with and do maintain abstinent sexual lifestyle. Implications and suggestions are discussed. Tujuan studi ini adalah meneliti isu daya tarik terhadap sesama jenis kelamin (same sex attraction = SSA) di antara anggota gereja di Surabaya. Studi ini memakai pendekatan kualitatif dan kuantitatif, untuk mengungkap pengajaran para pemimpin gereja, sikap anggota gereja, dan pengalaman SSA. Enam pemimpin gereja dari enam gereja di Surabaya, diwawancarai dengan wawancara semi-terstruktur dan 268 remaja gereja mengisi kuesioner tentang SSA. Hasil menunjukkan bahwa mayoritas pemimpin gereja dan remaja gereja memiliki sikap konservatif terhadap SSA. Sejumlah 5.6% partisipan pernah mengalami SSA dalam hidupnya. Serupa dengan remaja gereja pada umumnya, kebanyakan mereka setuju dengan atau bergaya hidup abstinen secara seksual. Didiskusikan implikasi dan saran-saran.